Part II: Training fast twitch muscle fibers: why and how - Maglischo, E. W. (Journal of Swimming Research, 2012)
With the finding that short, intense sprints can improve aerobic capacity (45), there has been a huge increase in the number of experts who advocate this kind of training over traditional endurance training. Several successful swim coaches are among those recommending more high-intensity training while an equal or even greater number are warning of the pitfalls of training in this manner. A theory is presented in this paper that high-intensity training is essential for improving aerobic endurance. An argument is also presented for a balanced approach to training that includes adequate quantities of moderate, and low-intensity swimming.